Publish or perish: Meet the editors a special panel. Issue 1 (27th December 2016) - Beheshti, Jamshid; Jansen, Jim; Dillon, Andrew; Lewandowski, Dirk; Mostafa, Javad; Khanova, Julia; Wilson, Tom; Seadle, Michael
ABSTRACT: This is a special panel to introduce the editors of prestigious international journals in library and information science, who will discuss the aim and the scope of the journals and elaborate on the expectations from potential contributors to help young academics understand and appreciate the process of academic publishing.